Strategi Diferensiasi Proses Berbasis Pixton: Solusi Inovatif Bagi Pembelajaran Menulis Bahasa Jerman di SMA - Tri Wahyuni; Udjang Pr. M. Basir (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Students’ writing proficiency in German language classes at SMAN 1 Driyorejo remains generally low, despite its significance for fostering deeper linguistic understanding. To address this challenge, process differentiation strategiesincluding the innovative use of Pixton media are essential for improving writing skills. This study analyzes how Pixton supports process differentiation as an innovative solution for German writing instruction in high schools. Using a qualitative descriptive approach, data were collected through in-depth interviews and literature review, then analyzed thematically. Findings reveal that process differentiation enables personalized learning aligned with students’ abilities and learning styles, while Pixton provides an engaging platform for expressing ideas through visual storytelling. The study recommends that educators adopt adaptive and responsive teaching practices to better address students’ needs in German language learning.